Cheap on Crime : Recession-Era Politics and the Transformation of American Punishment - Aviram, Hadar (University of California Press, 2015)
After forty years of increasing prison construction and incarceration rates, winds of change are blowing through the American correctional system. The 2008 financial crisis demonstrated the unsustainability of the incarceration project, thereby empowering policy makers to reform punishment through fiscal prudence and austerity. In Cheap on Crime, Hadar Aviram draws on years of archival and journalistic research and builds on social history and economics literature to show the powerful impact of recession-era discourse on the death penalty, the war on drugs, incarceration practices, prison heal.